Implementation and analysis of an updating data strategy on iot-waspmote gases testbed with 2.4 ghz xbee for air quality application - Alduais, N.A.M.; Abdullah, Noryusliza; Abdullah, J; Jamil, A; H. Y. Saad, Abdul-Malik
Battery life is a key factor in the performance of the Internet of Things (IoT) applications. The size and number of transmitted packets are responsible for most of the energy consumption in IoT applications. Therefore, controlling XBee operations (ON / OFF) based on the status of the sensed data is one of the possible ways to decrease the number of messages sent by a sensor node, thereby saving power and extending the network lifetime. Hence, this paper provides an implementation and analysis of an update data strategy on loT-Waspmote Gases Testbed with 2.4 GHz XBee. The studied algorithm enables efficient data collection and dissemination (EDCD) for IoT sensor board denoted as EDCD1 and EDCD2 for sensor board with a single sensor and multiple sensors, respectively. The EDCD has been applied on loT- Waspmote gases testbed for monitoring the air quality in various locations(Areas). The experimental results indicate that the EDCD algorithm performance is affected by the type of sensor as well as the sensing area/location. Overall, EDCD algorithm showed acceptable performance for IoT-Waspmote Gases Testbed with 2.4 GHz XBee. In addition, there is no delay in receiving data from the sensor node after applying the algorithm compared to directly transmitting data